Beyond Social Protection: Advancing Economic Independence Among Family Hope Program Beneficiaries In Sidoarjo - Rizza Nur Rahayu; Vera Firdaus; Sigit Hermawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effectiveness of business management education, community empowerment, and willpower on entrepreneurial motivation and economic independence for KPM of the Family Hope Program (PKH) in Sidoarjo District. This study uses a quantitative method to analyze the influence of independent variables, namely business management education, community empowerment and willpower, on the dependent variable consisting of entrepreneurial motivation and economic independence for KPM (Beneficiary Families) of PKH (Family Hope Program) in Sidoarjo District. The research location to test the hypothesis is in the study at KPM PKH Sidoarjo District. The number of respondents in this study is estimated at 150 people. The expected results are that each independent variable influences the dependent variable and the independent variables have a positive and significant effect together on the dependent variable.